Tocolytic activity of the Lippia alba essential oil and its major constituents, citral and limonene, on the isolated uterus of rats. (5th January 2019) - Pereira-de-Morais, Luís; Silva, Andressa de Alencar; da Silva, Renata Evaristo Rodrigues; Costa, Roger Henrique Sousa da; Monteiro, Álefe Brito; Barbosa, Cristina Rodrigues dos Santos; Amorim, Thaís de Souza; de Menezes, Irwin Rose Alencar; Kerntopf, Marta Regina; Barbosa, Roseli
Abstract: The species Lippia alba (Mill.) N. E. Brown belongs to the Verbenaceae family. It is abundant and grows spontaneously throughout the Brazilian territory. Popularly known as "erva-cidreira", it is widely used because of its sedative, carminative and analgesic properties. The objective of this study was to investigate the mechanism of action of the L. alba essential oil (EOLa) and its major constituents citral and limonene, on isolated rat uterus muscle. To evaluate the EOLa, citral and limonene effect, cumulative concentrations curves for EOLa and citral (1–600 μg/mL) and for limonene (1–1200 μg/mL) were constructed from contractions of rat uterine strips under a 1 g tension. EOLa, citral and limonene dose-dependently relaxed myometrial preparations pre-contracted with 60 mM KCl, 10-2 IU/mL oxytocin, serotonin (10 μM), or ACh (10 μM). The results demonstrate that the EOLa, citral and limonene cause relaxation of the uterine smooth muscle. These results suggest that the relaxation induced by EOLa, citral and limonene is caused by inhibition of L-type VOCC, inhibiting the Ca 2+ current through these channels, although other mechanisms of action are likely to contributing to relaxant activity. There was no involvement of K + channels (BKca, KATP, KV ) or cyclooxygenase on the relaxation promoted by EOLa. Then studies of the tocolytic effects of EOLa, citral and limonene may yield new insights into their therapeutic use. Graphical abstract: Highlights: Essential oil of the Lippia alba present major constituents as citral and limonene. The essential oil of the Lippia alba present tocolytic activity. The essential oil of the Lippia alba blocked contractions of rat uterine muscles. Tocolytic action may be associated with the regulation of Ca +2 by VOOC.